(untitled) (Medical Forum Monthly, 2022)
Objective: To find out common site, histological type and nodal metastasis in the SCC patients visiting outdoor of NID. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the department of Oral and maxillofacial surgery (surgical unit 2), NID, Multan, Pakistan from July 2021 to February 2022. Materials and Methods: Total 112 patients of both genders and all age groups were included. The parameters assessed were site of the lesion, histological type and presence or absence of cervical lymphadenopathy. Diagnosis of SCC was made with proper history, clinical examination and histopathology. The demographic data of all the subjects were recorded on a structured questionnaire; they were also asked about harmful habits like betel nut and quid chewing, snuff dipping, cigarette smoking and alcohol intake. Results: In our study, age of mostly patients was in between 41-61years. Mean age was 50.7±2.5. In this study 53.57% were males, in 34.82% of cases lesion was on buccal mucosa and 43.75% patients had well differentiated carcinoma. Most of the patients in this study showed metastasis to lymph nodes N2b (42.85%), while 33.03% patients had no lymph node involvement at all. Conclusion: Oral SCC affects both genders but the ratio of males is slightly higher. Chiefly, buccal mucosa was involved, common histopathological pattern was Grade I followed by Grade II and several patients reported with associated cervical lymphadenopathy.